Decompressive hemicraniectomy in malignant middle cerebral artery infarction: the ‘real world' beyond studies - Pledl, Hans-Werner; Hoyer, Carolin; Ebert, Anne; Seiz-Rosenhagen, Marcel; Arp, Mirko; Hennerici, Michael G.; Alonso, Angelika (European neurology, 2016)
Background: Decompressive hemicraniectomy (DHC) is life-saving in patients with malignant middle cerebral artery infarction (MMI), but outcome, perspectives and complications after DHC in daily practice are largely unknown. Methods: From 2008 until 2014, we extracted patient's characteristics as well as complications from our database for patients with MMI who underwent DHC. Additionally, we analysed medical records from the different rehabilitation steps. Results: We identified 48 consecutive patients (mean 57 years, 21 male, 41.7% >60 years) with MMI who underwent DHC. The decision for DHC was made on an individual basis, including patients without impaired consciousness or stroke onset >48 h. In-hospital patients achieved only marginal clinical improvement. Seventy-five percent attended an early-rehabilitation, 44% achieved post-stroke rehabilitation and 6% carried on late-stage rehabilitation. In all, 45.5% returned home after rehabilitation. In-hospital mortality was 14.6%, overall mortality was 16.7%. Surviving patients (78.9%) had a modified Rankin Scale of 4-5. Frequent neurologic complications were symptomatic epilepsy and delirium. Following DHC/bone-flap-reimplantation, wound-healing disorders, epidural hematoma and wound infections were major surgery-related complications. Pulmonary infections were frequent in the acute-phase and urinary tract infections were predominant in the late-phase. Conclusions: DHC is a life-saving technique in patients with MMI, but complications are frequent, were underestimated in randomized clinical trials and may worsen the functional outcome.
Gesehen am 13.02.2019